The Potential of Bio-Innovation - Karembu, Margaret (2019)
Margaret Karembu COUNTRY WORKSHOP The Knowledge Lab on Climate Resilient Food Systems: An analytical support facility to achieve the SDGs Co-Organized by IFPRI and AGRA FEB 7, 2019 - 08:30 AM TO 05:55 PM EAT